Pesantren-Based Recruitment and Selection Model - Nanda Hidayan (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2026)
Recruitment and selection are strategic functions in human resource management that aim not only to acquire competent employees but also to ensure value alignment between the individual and the organization. In the context of Islamic boarding schools, this process possesses unique characteristics, as it integrates professional competence with Islamic boarding school values ​​that define the institution's identity. This study aims to analyze the Islamic boarding school value-based employee recruitment and selection model at Pondok Pesantren Salafiyah Syafi'iyah Sukorejo, Situbondo. A qualitative approach with a case study design was employed. Data were collected through observation, interviews, and documentation, then analyzed using the interactive model developed by Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing. The results indicate that the recruitment and selection process is carried out in five stages: identifying staffing needs based on institutional requirements; recruitment based on competence and khidmah (devoted service); selection based on person-organization fit; internalizing the values ​​of amanah (trustworthiness), ikhlas (sincerity), and barokah (divine blessing) in decision-making; and initial orientation grounded in Islamic boarding school culture. The findings confirm that recruitment and selection serve not merely as mechanisms for acquiring staff but also as instruments for talent development, generational renewal, and the preservation of organizational culture. The study's novelty lies in the formulation of a "Pesantren-Based Recruitment Model" that integrates a Value-Based Human Resource Management approach with the concept of Person-Organization Fit within the context of a Islamic boarding school organization. This model offers a theoretical contribution to the development of value-based human resource management and serves as an alternative human resource management practice for Islamic educational institutions striving to balance professionalism with Islamic boarding school values.